2013
DOI: 10.3340/jkns.2013.53.6.342
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Anatomic Outcome Scales of Coiled Intracranial Aneurysms in the Prediction of Recanalization

Abstract: ObjectiveSeveral scales are currently used to assess occlusion rates of coiled cerebral aneurysms. This study compared these scales as predictors of recanalization.MethodsClinical data of 827 patients harboring 901 aneurysms treated by coiling were retrospectively reviewed. Occlusion rates were assessed using angiographic grading scale (AGS), two-dimensional percent occlusion (2DPO), and volumetric packing density (vPD). Every scale had 3 categories. Followed patients were dichotomized into either presence or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…AV and rupture status has already been identified as a significant risk factor for recanalization in previous studies [ 3 , 7 , 12 , 18 , 21 , 22 ]. Our results are consistent with those findings.…”
Section: Discussionmentioning
confidence: 98%
“…AV and rupture status has already been identified as a significant risk factor for recanalization in previous studies [ 3 , 7 , 12 , 18 , 21 , 22 ]. Our results are consistent with those findings.…”
Section: Discussionmentioning
confidence: 98%
“…More cautious follow-up is indispensable for large, ruptured, or wide-necked aneurysms. For a good angiographic result immediately after treatment, advanced techniques such as the balloon-assisted technique4 14 15 and newly developed devices such as complex-shaped coils,16 unique configuration coils,17 thick coils,18 bioactive coils, and hydrogel-coated coils19 20 have been used. An operator technique that has been found to avoid compaction is to insert as many coils as possible in cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some evidence, however, that PD is not as influential in certain subgroups [26][27][28]. In 2005, Goddard et al found that PD (or coil-embolization ratio, as it was named in their study) was not predicative of recurrence, specifically for small intracranial aneurysms (defined as <7 mm) [27].…”
Section: Pdmentioning
confidence: 99%